Okonkwo’s Tragic Flaws in Chinua Achebe’s Things Fall Apart and Judas Iscariot in the New Testament: Paradigm for Nigerian Politicians - Ottuh, John Arierhi (NIU Journal of Humanities, 2018)
Using the comparative analysis paradigm as a method, the study aimed at comparing Okonkwo’s tragic flaws in Chinua Achebe’s things fall apart with that of Judas Iscariot in the New Testament. The duo characters in view were victims of ego and greed respectively. The paper showed that Okonkwo’s tragic flaws in Chinua Achebe’s things fall apart and that of Judas Iscariot in the New Testament were that of strength and villain respectively. The paper also showed that a cultural and religious rift was created between imperialist dogmatism via colonialism and indigenous religious beliefs when the white missionaries introduced Christianity to Umuofia. Keywords: Okonkwo, Tragic Flaws, Chinua Achebe, Judas, New Testament, Nigeria